International educational innovation and public sector entrepreneurship - Wiseman, Alexander W., 1968- (Bingley, U.K. : Emerald, 2013)
The internationally comparative perspective of the volume will frame educational innovation and social entrepreneurship using both the globalization and contextualization of educational quality and opportunity in disadvantaged communities worldwide as a foundation. Through the use of both empirical research reports and case study examples, this volume will examine the contributions of social entrepreneurs through educational programs, projects and systems worldwide, and how the social, cultural and political communities in each nation contextualize educational innovations. Chapters will examine evidence to assess the impact of social entrepreneurship in education and to make recommendations for innovative educational change. This volume will also highlight the importance of theory in both understanding and guiding innovative ideas in every stage of entrepreneurial development from research-to-practice.
Internationally comparative approaches to innovation and entrepreneurship in education / Alexander W. Wiseman -- Youth entrepreneurship education and training for poverty alleviation : a review of international literature and local experiences / Aryn Baxter ... [et al.] -- Socio-educational entrepreneurship within the public sector : leveraging teacher-driven innovations for improvement / Vijaya Sherry Chand -- Developing innovation and entrepreneurial skills in youth through mass education : the example of ICT in the UAE / Alexander W. Wiseman, Emily Anderson -- The impact of public sector entrepreneurship in international education on skilled migration / Radu Daniel Prelipcean ... [et al.] -- Social entrepreneurship and information and communication technologies in Ecuador : examples and opportunities / Matthew Aruch, Ana Loja, James B. Sanders -- What about students' right to the "right" education? An entrepreneurial attitude to teaching and learning / Eva Leffler, ôsa Falk-Lundqvist -- Entrepreneurs in private higher education : a case study of education entrepreneurs in a middle income economy / Seng P. Yeoh -- Promises and challenges for innovation and entrepreneurship in education / Alexander W. Wiseman.
Includes index.
Print version record
Keywords: Education -- General; Education; Entrepreneurship; Educational innovations; Education; Political entrepreneurship